2022
DOI: 10.3390/nano12213853
|View full text |Cite
|
Sign up to set email alerts
|

Dual Tunable Electromagnetically Induced Transparency Based on a Grating-Assisted Double-Layer Graphene Hybrid Structure at Terahertz Frequencies

Abstract: We propose a graphene plasmonic structure by applying two graphene layers mingled with a thin gold layer in a silicon grating. By utilizing the finite-difference time-domain (FDTD) method, we investigate the optical response of the system, and observe that the design achieves dual tunable electromagnetically induced transparency (EIT)-like effect at terahertz frequencies. The EIT-like effect arises from the destructive interference between the grapheme-layer bright modes and the gold-layer dark mode. The EIT-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Another interesting phenomenon observed is the tuneable terahertz response of SLG under the application of varying external voltage. However, few theoretical and experimental studies on the THz signal of graphene are reported which are based on ultrafast electric field and gate voltage, 5 the optical response based on the grating assisted plasmonic structure of double layer graphene with a Au layer in between, 27 a tuneable THz wave modulator, 28 power dependent spectral characteristics of single layer graphene, 29 ultrafast photocurrent in dual-gated graphene using pump-probe spectroscopy and the thermoelectric effect, 30 variation in electrical conductivity of graphene on different substrates by THz signal mapping of graphene 31 and broadband graphene terahertz modulators enabled by intraband transitions. 32 To the best of our knowledge, no one has yet reported anywhere in the literature about the tuneable terahertz response of SLG under the application of varying external voltage.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting phenomenon observed is the tuneable terahertz response of SLG under the application of varying external voltage. However, few theoretical and experimental studies on the THz signal of graphene are reported which are based on ultrafast electric field and gate voltage, 5 the optical response based on the grating assisted plasmonic structure of double layer graphene with a Au layer in between, 27 a tuneable THz wave modulator, 28 power dependent spectral characteristics of single layer graphene, 29 ultrafast photocurrent in dual-gated graphene using pump-probe spectroscopy and the thermoelectric effect, 30 variation in electrical conductivity of graphene on different substrates by THz signal mapping of graphene 31 and broadband graphene terahertz modulators enabled by intraband transitions. 32 To the best of our knowledge, no one has yet reported anywhere in the literature about the tuneable terahertz response of SLG under the application of varying external voltage.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the graphene layer is unnecessary for the patterning process, and it thus has great advantages in machinability and processing difficulty, which greatly improves the applicability of graphene. In 2022, Zhong et al 18 . proposed a graphene structure by applying two graphene layers mingled with a thin gold layer in a silicon grating and achieved a dual tunable EIT-like effect at terahertz frequencies.…”
Section: Introductionmentioning
confidence: 99%